1988
DOI: 10.1002/jmv.1890250402
|View full text |Cite
|
Sign up to set email alerts
|

Virus isolation and immune studies in a cohort of homosexual men

Abstract: Virus shedding was detected in 77% of homosexual subjects and in only 6% of heterosexual controls. The overall virus isolation rate in homosexual subjects was not significantly different among HIV-seropositive (79%) and HIV-seronegative (74%) individuals. In about 20% of homosexual subjects, virus shedding from multiple sites was observed. The most frequently isolated virus was cytomegalovirus (CMV) (41%), followed by enteroviruses (23%), herpes simplex virus (HSV) (7%), and adenoviruses (6%). In the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
3
15
4
Order By: Relevance
“…The pattern of virus shedding in Ad5hr-infected RM mirrors Ad5hr shedding in humans. Adenovirus shedding from the lower GI tract is common in children during symptomatic and asymptomatic infections and it also occurs in healthy adults [36][39]. A recent study found adenoviruses in 7.1% of approximately12,000 respiratory samples from pediatric populations with respiratory symptoms, and there was a high rate of adenovirus co-infection (21.7%) with multiple serotypes in many positive samples [40].…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of virus shedding in Ad5hr-infected RM mirrors Ad5hr shedding in humans. Adenovirus shedding from the lower GI tract is common in children during symptomatic and asymptomatic infections and it also occurs in healthy adults [36][39]. A recent study found adenoviruses in 7.1% of approximately12,000 respiratory samples from pediatric populations with respiratory symptoms, and there was a high rate of adenovirus co-infection (21.7%) with multiple serotypes in many positive samples [40].…”
Section: Discussionmentioning
confidence: 99%
“…We observed viral shedding in 75% of study participants, who collectively yielded at least 20 different HAdV types including four potentially new types and two additional variants of type 48. Several previous studies have examined the prevalence of enteric viruses in a variety of populations [2], [3], [4], [5], [6], [7], [8], [10], [11], [12], [13], [14], [37], [38], [39], [40], [41], [42], [43], [44]. While HAdV infections in otherwise healthy individuals generally manifest as transient infections with complete resolution, numerous studies have demonstrated the potential for these viruses to establish prolonged and/or latent infection in a variety of sites including adenoidal tissue [45], peripherally circulating mononuclear cells [46], the urinary tract [44], the conjunctiva [47], and the GI tract [9], [11].…”
Section: Discussionmentioning
confidence: 99%
“…HAdVs are grouped into seven species, A–G, and further subdivided into at least 52 known types. HAdV shedding from the lower GI tract may occur in healthy adults [3], [4], [5], but is more common in children (where it may represent a primary infection) [6], [7], [8], [9], immunocompromised individuals [2], and persons with HIV infection, particularly those with symptomatic infection and low CD4 counts [3], [10], [11], [12]. In HIV-infected individuals, HAdV shedding has been associated with lower gastrointestinal symptoms such as diarrhea and proctitis in some [3], [13], [14] but not all studies [5], [10], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Cofactors that have been demonstrated to alter the probability of acquisition of HIV and/or the rate at which AIDS subsequently develops include: cytomegalovirus (CMV) (Emery et al, 1999;Kovacs et al, 1999;Robain et al, 2001;Sabin et al, 1995;Sever et al, 1995;Webster, 1991), heptatitis viruses B and C (HBV and HCV) (Antipa et al, 1995;Twu et al, 1993), herpes viruses 2, 6, and 8 (HSV1, HSV2, HHV6, HHV8) (Buimovici-Klein et al, 1988;Perez et al, 1998;Sever et al, 1995;Sonnabend, 1989), Mycobacterium tuberculosis (MTb) (Goletti et al, 1996;Maserati et al, 1999;Whalen et al, 1995), a variety of mycoplasmas, including M. fermentans, M. hominis, M. pirum, M. penetrans, and M. genitalium (Al-Harthi et al, 1999;Ballard et al, 2002;Cordova et al, 2000;De Cordova et al, 1999;Faye-Kette et al, 2000;Grau et al, 1998;Hakkarainen et al, 1992;Olinger et al, 1999;Perez et al, 1998), and Staphylococcus aureus, which is a particularly frequent infection among those who acquire HIV via intravenous drug use (Brinchmann et al, 1992;Goujard et al, 1994).…”
Section: Introductionmentioning
confidence: 97%
“…People at risk for acquired immunodeficiency syndrome (AIDS) are characterized by unusually high rates of infection with so-called cofactor infections before, during, and after infection with HIV (Bentwich et al, 1995;Buimovici-Klein et al, 1988;Montagnier, 2002;Quinn et al, 1987;RootBernstein, 1990a,b;Root-Bernstein and Hobbs, 1993;Sonnabend, 1989). Cofactors that have been demonstrated to alter the probability of acquisition of HIV and/or the rate at which AIDS subsequently develops include: cytomegalovirus (CMV) (Emery et al, 1999;Kovacs et al, 1999;Robain et al, 2001;Sabin et al, 1995;Sever et al, 1995;Webster, 1991), heptatitis viruses B and C (HBV and HCV) (Antipa et al, 1995;Twu et al, 1993), herpes viruses 2, 6, and 8 (HSV1, HSV2, HHV6, HHV8) (Buimovici-Klein et al, 1988;Perez et al, 1998;Sever et al, 1995;Sonnabend, 1989), Mycobacterium tuberculosis (MTb) (Goletti et al, 1996;Maserati et al, 1999;Whalen et al, 1995), a variety of mycoplasmas, including M. fermentans, M.…”
Section: Introductionmentioning
confidence: 98%